Transhumanism, transmedia and the Serial podcast: Redefining storytelling in times of enhancement - Baelo-Allué, Sonia (International Journal of English Studies, 2019)
The digital age has facilitated the creation of fluid, open stories that are subject to change as they unfold across different media platforms, each contributing to the story as a whole. Transmedia storytelling is also linked to transhumanism, a philosophy based on the idea that human limitations can be overcome through reason, science and technology to finally free us from the limitations of our bodies and minds. The concept of the literary has changed because the concept of the human has also evolved, as technology has been used to enhance both human capacities and storytelling through active participation, group work, and collective intelligence. This double enhancement that transmedia and transhuman storytelling entail is explored in this article through a textual and paratextual analysis of Serial, the world’s most popular podcast, which can help us redefine the present blurring of disciplinary boundaries and the new territory of the literary.